(3GdQhV GdHGSe aj MhGOK GdYeQ hGdJQGLes - (3YHO GdHGSW Hf Ndjd Hf TGgjf GdedWj, Ke GdbGgQj, Rjf GdOjf,J (B920 (3g` s
(3ChdgG (B:s
(3ef JcedI JQLeI GdCTQa bGjJHGi bhdg HOhfgG cPdc MJi Hjf GdfSGA hCRhGLgf s
(3BNQgG (B:s
(3aUdi Ydjg Ke CXgQ GdJCSa Ydjg Ydi eG fbdg GdHYV hMed Edi JQHJg aOafhg HgG hGdMeO ddg hMOg Je s
(3Hg fbY eGAs
(3ef HbjI MhGOK SfI (B872_874s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs